Bone marrow cell transcripts from Fanconi anaemia patients reveal in vivo alterations in mitochondrial, redox and DNA repair pathways. (15th June 2013) - Pagano, Giovanni; Talamanca, Annarita Aiello; Castello, Giuseppe; d'Ischia, Marco; Pallardó, Federico V.; Petrović, Sandra; Porto, Beatriz; Tiano, Luca; Zatterale, Adriana
Abstract: Fanconi anaemia (FA) is a genetic cancer predisposition disorder associated with cytogenetic instability, bone marrow failure and a pleiotropic cellular phenotype, including low thresholds of responses to oxidative stress, cross‐linking agents and selected cytokines. This study was aimed at defining the scope of abnormalities in gene expression using the publicly available FA Transcriptome Consortium (FTC) database (Gene Expression Omnibus, 2009 and publicly available as GSE16334). We evaluated the data set that included transcriptomal analyses on RNA obtained from low‐density bone marrow cells (BMC) from 20 patients with FA and 11 healthy volunteers, by seeking to identify changes in expression of over 22 000 genes, including a set of genes involved in: (i) bioenergetic pathways; (ii) antioxidant activities; (iii) response to stress and metal‐chelating proteins; (iv) inflammation‐related cytokines and (v) DNA repair. Ontological analysis of genes expressed at magnitudes of 1.5‐fold or greater demonstrated significant suppression of genes in the categories of (i) energy metabolism; (ii) antioxidant activities; and (iii) stress and chelating proteins. Enhanced expression was found for 16 of 26 genes encoding inflammatory cytokines. A set of 20 of 21 transcripts for DNA repair activities were down‐regulated; four of these transcripts related to type II topoisomerase. The data provide evidence for alterations in gene regulation of bioenergetic activities, redox‐related activities, stress and metal‐chelating proteins, and of some selected DNA repair activities in patients with FA.